2020
DOI: 10.3389/fpls.2020.00459
|View full text |Cite
|
Sign up to set email alerts
|

Increased Glyphosate-Induced Gene Expression in the Shikimate Pathway Is Abolished in the Presence of Aromatic Amino Acids and Mimicked by Shikimate

Abstract: The herbicide glyphosate inhibits the plant enzyme 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) in the aromatic amino acid (AAA) biosynthetic pathway, also known as the shikimate pathway. Amaranthus palmeri is a fast-growing weed, and several populations have evolved resistance to glyphosate through increased EPSPS gene copy number. The main objective of this study was to elucidate the regulation of the shikimate pathway and determine whether the regulatory mechanisms of glyphosate-sensitive and glyphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 62 publications
4
15
0
Order By: Relevance
“…By far, the most highly accumulated metabolite after glyphosate is shikimate so that its content is commonly used as an indicator of glyphosate sensitivity [ 27 , 31 , 32 , 33 ]. Moreover, recently it has been demonstrated that several metabolic disturbances elicited after glyphosate treatments are mediated by shikimate accumulation, as glyphosate effects were mimicked in plants supplemented with exogenous shikimate [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…By far, the most highly accumulated metabolite after glyphosate is shikimate so that its content is commonly used as an indicator of glyphosate sensitivity [ 27 , 31 , 32 , 33 ]. Moreover, recently it has been demonstrated that several metabolic disturbances elicited after glyphosate treatments are mediated by shikimate accumulation, as glyphosate effects were mimicked in plants supplemented with exogenous shikimate [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that low‐dose stress triggers plant tolerance mechanisms, protecting plants against subsequent high‐level environmental stress 9 . Plant adaptive responses are somewhat specific to environmental factors, since these responses are designed to eliminate specific disruptions by stressors 10–13 . However, it remains unclear whether stimulated traits of plant hormesis induced by mild stressors differ, and how non‐specific (due to the need to activate functions relevant to survival and suppress other functions with any stress impacts) and specific (by the nature of the factor and the ‘points’ of its impact on plant metabolism) adaptive mechanisms contribute to hormesis stimulation in plants 14 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Plant adaptive responses are somewhat specific to environmental factors, since these responses are designed to eliminate specific disruptions by stressors. [10][11][12][13] However, it remains unclear whether stimulated traits of plant hormesis induced by mild stressors differ, and how non-specific (due to the need to activate functions relevant to survival and suppress other functions with any stress impacts) and specific (by the nature of the factor and the 'points' of its impact on plant metabolism) adaptive mechanisms contribute to hormesis stimulation in plants. 14 Understanding how plants adapt to environmental stressors is necessary to provide foundation theories to elicit a consistent response allowing researchers to identify the likely processes leading to greater productivity or stress tolerance, which is important for improving agricultural production and food security.…”
Section: Introductionmentioning
confidence: 99%
“…Several enzymes are involved in amino acid biosynthesis in plants, with each enzyme providing a specific function. For example, the production of aromatic AAs necessary for plant metabolism, such as L-tryptophan and L-phenylalanine, depends on the shikimate pathway ( Zulet-Gonzalez et al., 2020 ; Bergman et al., 2022 ; Kanaris et al., 2022 ). 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase (DAHP) is an important enzyme in controlling carbon entering the shikimate pathway ( Mir et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%